Development of Cost Analysis Process based on the Supply Chain Strategy - Vladimir Nikolaevich Nesterov; Dina Gennadevna Yankovskaya; Natalia Nikolaevna Kozlova (International Journal of Supply Chain Management, 2020)
Abstract— This paper discusses the methodology of research and development costs analysis through the supply chain management. Peculiarities of costs formation at early stages of development life cycle are defined, aims and tasks of analysis, method of cost budget analysis in terms of responsibility centers, individual projects and cost items are disclosed. The supply chain management discipline suggests that information sharing is paramount when attempting to achieve cost reductions and quality improvements. Factors have been identified and impact of such factors on costs assessed. Special attention is devoted to the ratio between costs and results and to the ratio between costs and work duration. The analysis of plan and fact costs of separate projects is carried out in supply chain process and by examples of projects creation is considered. Besides that, the algorithm of average costs estimation through the determination of dependence between costs and work duration are presented by formula. The research identifies a theoretical model that can be used to explain the relationships and themes associated with supply chain costing and strategic decision making. Evidence suggests that there is some movement to implement managerial accounting techniques within these two industries to capture supply chain costing information. The results of this study allow to make decisions by supply chain managers for increasing of research and development work efficiency and for cost reduction.